A New Approach to Reducing Payments Made to Hospitals with High Complication Rates - Richard L. Fuller; Elizabeth C. McCullough; Richard F. Averill (SAGE Publishing, 2011)
This article proposes a redesign of the Medicare inpatient prospective payment system to reduce payments made to hospitals with high complication rates. We compute risk-adjusted, expected complication rates for hospitals and compare them to actual complication rates in order to determine the number of excess complications. Hospital payment reductions then are computed based on the number of excess complications in a hospital. Medicare hospital payment could be reduced by approximately 8% ($8.5 billion) if hospitals were held to a "best practice" standard and if payments made for excess complications were eliminated.